Trustworthy identity system based on IPv6 source address validation - Duan-qi ZHOU; Jun BI; Guang YAO (Tongxin xuebao)
In the Internet,there are no mechanisms to verify the identity of a message sender,resulting in a large number of forged identity attacks,such as phishing websites.By mapping the user identity into the rightmost 64 bit of the IPv6 address,this paper tries to make every message embedded with an identity,which lay a credible foundation for communications on the Internet.We design and realize a true identity communication system based on source address validation improvement,which can protect the privacy of the users,and ensure the verifiability and authenticity of the user identities.